2019
DOI: 10.4269/ajtmh.17-0546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Response Time in Zanzibar’s Malaria Elimination Case-Based Surveillance–Response System

Abstract: As countries transition toward malaria elimination, malaria programs rely on surveillance-response systems, which are often supported by web-and mobile phone-based reporting tools. Such surveillance-response systems are interventions for elimination, making it important to determine if they are operating optimally. A metric to measure this by is timeliness. This study used a mixed-methods approach to investigate the response time of Zanzibar's malaria elimination surveillance-response system, Malaria Case Noti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Both methods are hampered by the development of insecticide resistance [26], while LLINs are ineffective against diurnal Aedes mosquitoes. Nonetheless, these efforts have contributed to a dramatic reduction in malaria prevalence and incidence in Zanzibar [26][27][28]. Whereas malaria cases are declining, ongoing waste generation, unreliable domestic water supply creating a demand for localized water storage, and environmental and climatic changes seem to be favoring the proliferation of Aedes mosquitoes [24,29].…”
Section: Introductionmentioning
confidence: 99%
“…Both methods are hampered by the development of insecticide resistance [26], while LLINs are ineffective against diurnal Aedes mosquitoes. Nonetheless, these efforts have contributed to a dramatic reduction in malaria prevalence and incidence in Zanzibar [26][27][28]. Whereas malaria cases are declining, ongoing waste generation, unreliable domestic water supply creating a demand for localized water storage, and environmental and climatic changes seem to be favoring the proliferation of Aedes mosquitoes [24,29].…”
Section: Introductionmentioning
confidence: 99%
“…A previous evaluation of the MCN system suggested that operational issues such as mobile phone network failures and delays in obtaining funds for refueling DMSO motorbikes may at times lead to delays in case review and household follow-up. 27 The standard number of two DMSOs per district irrespective of the district's area, population size, or expected malaria incidence may, at particular times of the year or days of the week, be insufficient. The program has, therefore, made changes including hiring a larger number of DMSOs in some districts to compensate for this.…”
Section: Operational Coverage Of Reactive Case Detection In Zanzibarmentioning
confidence: 99%
“…Data collected by malaria posts, including the number of positive cases and the number of consultations, are crucial in the planning and timely delivery of necessary targeted interventions in areas of high P. falciparum burden [ 4 ] or in response to increases in incidence in low transmission settings, in the monitoring of intervention impact, and in responding to decreases in malaria post service uptake. However, the utility of the data depends on how quickly it is collected, analysed, and responded to [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%